2021
DOI: 10.3390/agronomy11020319
|View full text |Cite
|
Sign up to set email alerts
|

The Adoption of Landraces of Durum Wheat in Sicilian Organic Cereal Farming Analysed Using a System Dynamics Approach

Abstract: The adoption of rare, traditional crops represents a good example of enhancing functional agrobiodiversity, not only to provide benefits for farmers but also for society as a whole. The study outlined in this paper aims to verify how and under local social-ecological conditions the combination of organic cereal farming and growing of durum wheat landraces can be profitably applied. Focusing on Sicily as one of the most developed cereal systems existing in southern Italy, the study deployed a comparison between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…From the analysis of the material collected, it was identified that in fact the theme is recent, given that the oldest publication, through the search filter adopted, is from 2015. Also, there is a propensity for studies to belong to the rural area (Lapeyre et al, 2015b;van Noordwijk, 2019;van Noordwijk et al, 2014;Varia et al, 2020). Such evidence goes to meet what Pagiola et al (2013) they argue.…”
Section: Brown Et Al (2022)mentioning
confidence: 79%
“…From the analysis of the material collected, it was identified that in fact the theme is recent, given that the oldest publication, through the search filter adopted, is from 2015. Also, there is a propensity for studies to belong to the rural area (Lapeyre et al, 2015b;van Noordwijk, 2019;van Noordwijk et al, 2014;Varia et al, 2020). Such evidence goes to meet what Pagiola et al (2013) they argue.…”
Section: Brown Et Al (2022)mentioning
confidence: 79%
“…Different social actors (farmers, breeders, processors, advisors, communicators, researchers, chefs and other stakeholders) belong to the association. In 2020, there were 181 firms associated, of which 129 were farms, 13 were mills, 10 were bakeries, 3 were small-medium pasta factories, and the rest conducted other types of business [46].…”
Section: Resultsmentioning
confidence: 99%
“…Use of the traditional landrace Saragolla Lucana may support differentiated farm strategies in highly competitive and demanding markets. Thanks to globalization and the homogenization of food and fiber products, consumers are becoming more and more demanding of higher quality, safe, and tasteful (traditional) goods [94,95]. Consumers associate tradition with native varieties of durum wheat and recognize traditional pasta made from landrace varieties worthy of higher economic value [96].…”
Section: Discussionmentioning
confidence: 99%